Histomorphological and Biochemical Changes Induced in Male Wistar Rats by Chronic Oral Doses of Piper guineense Schumach. & Thonn. - Dennis, Kpomah Enyohwo; Bridget, Kpomah; Marcellinus, Arhoghro Ejovwoke (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Histopathological tissue (liver, kidney and testes) and biochemical changes were studied following chronic oral administration of graded doses of ethanol extract of Piper guineense Schumach. & Thonn on male wistar rats. Twenty healthy male rats weighing between 190 – 200 g were randomly divided into four groups (A – D) of five rats per group. Group A (control) were orally dosed once daily with 1 ml of the vehicle (distilled water), while the other three groups were administered with 50, 100 and 150 mg/kg body weight of the extract in 1 ml of the vehicle for 42 days treatment period. At the completion of the extract dosing period, the animals were anaesthetized, blood samples collected for biochemical assay (lipid parameters, liver enzymes and liver function test). Tissues were also excised (liver, kidney and testes) for histopathological examination. The liver of the treated groups showed mild to severe vesicular steatosis (fatty change) when compared to the control group which had well preserved lobular architecture, normal hepatocyte with no indication of inflammation. The kidney of the treated groups revealed varying degree of distortion in microanatomy of the cortex when compared to the control with normal histological features. The testes of the treated groups showed severe distortion of seminiferous tubules, no proper coordination between boundaries and delayed maturation of germ cells when compared to the control group with orderly maturation of germ cells. The values for biochemical assay are mean of five replicates ± standard deviation, the values were analyzed using one way analysis of variance (ANOVA) followed by Posthoc Turkey. The lipid parameters of total cholesterol and low density lipoprotein were significantly increased p < 0.05, high density lipoprotein was significantly decreased p < 0.05, while there was no significant change in triglyceride p > 0.05. All liver enzymes were significantly increased p < 0.05. Albumin, globulin, total and conjugated bilirubin were significantly increased p < 0.05 while the total protein was not significantly changed p > 0.05. Prolonged use of herbal formulation of p. guineense may herald hepatotoxicity, nephrotoxicity with impaired sexual/reproductive function in male wistar rats.